PHARMACOECONOMIC ANALYSIS OF USE OF PENTAVALENT COMBINATION VACCINE WITH ACELLULAR PERTUSSIS COMPONENT IN THE FRAMEWORK OF THE REGIONAL IMMUNIZATION SCHEDULE OF KRASNODAR FOR ALL CHILDREN AGED 0–18 MONTHS AND SEPARATLY FOR CHILDREN AT RISK - A. Yu. Kulikov; Yu. I. Akimova (Педиатрическая фармакология)
Introduction. On the one hand, extension of the immunization schedule provides protection from more infections; on the other hand, it increases the injection load, especially in young children. That is why inclusion of combination vaccines, which could help to reduce the amount of injections, is relevant. The study was aimed at conducting pharmacoeconomic evaluation of including combination pentavalent acellular vaccine against diphtheria, pertussis, tetanus, poliomyelitis, Haemophilus influenzae type b (DTaP-IPV/Hib) to the regional immunization schedule of Krasnodar for all children and separately for children at risk. Methods. Modeling; economic methods of estimation: cost-effectiveness analysis, cost-utility analysis, budget impact analysis. Results. Analysis yielded the following data: in terms of the healthcare system, 4 pentavalent vaccine injections will require additional costs of 1,316,533 rubles per unit of effectiveness and 1,298,846 rubles per unit of utility. In terms of the region and society, transition from the current scenario to a combination vaccine scenario will help to save 9,778,821 rubles in the entire cohort over the entire horizon period. In terms of the healthcare system, according to the budget impact analysis, transition from the current scenario to a DTaP scenario will require additional investments of 16,349,631 rubles, transition to a pentavalent vaccine scenario — 7,208,861 rubles; in terms of the region and society — 16,191,343 rubles and 7,050,573 rubles, respectively. Conclusions. In terms of the incremental cost-effectiveness and cost-utility analyses, scenario 1 (4 combination pentavalent vaccine injections) is strongly preferred (dominant) from the regional perspective and acceptable from the healthcare system’s perspective. According to the budget impact analysis and taking into account only the healthcare system’s costs, transition from the current immunization schedule to a combination vaccine schedule will requireadditional investments. However, it will help to reduce regional expenses, given the social and other expenses not covered by the healthcare system’s budget. In the event of vaccination of children at risk and comparison of reasonability of transition from the current immunization schedule to an acellular DTP (DTaP) schedule or a pentavalent combination vaccine schedule, the budget impact analysis demonstrated that transition from the current immunization schedule for children at risk to a pentavalent vaccine schedule is dominant in comparison with the perspective of transition to a schedule consisting in 4 DTaP injections.